Geo-Cultural: Educational Soft Power and Development - Naksamrit, Jareeporn (Journal of Cultural Approach, 2025)
This academic article explains the concept of “Cultural Landscape” in the context of Thai society. Currently, Thai society is paying attention to the power that comes from the roots of culture, “soft power,” which the author calls “Wattana Palang.” It is the power of seeking wealth within the framework of religion (MOC, 2018) or a way that emphasizes humanity or human evolution. It is a search for knowledge or values and virtues that can be shown in Thai culture in each region. It is necessary to study and rehabilitate, conserve, and preserve the natural values of the cultural landscape to further create social innovation, management, cultural prosperity, traditions, identity, and natural surroundings, which are applied to human development and are beneficial to the country, in which education plays an important role. We must consider bringing the issue of cultural landscape as a powerful educational utility to promote community development in the form of studying and investigating cultural practices. Database management, conservation, management through educational learning processes, environmental arrangement, organizing, and academic curricula for educational institutions further develop students and promote knowledge for teachers and personnel. Culture and practices create pride in one's uniqueness and a sense of love for one's homeland. Furthermore, it can promote it at an international level. This educational role must rely on educational leaders. In many countries, importance has been given to the foundations of culture, such as the learning resources of countries that have developed a learning culture through places and ruins. Nationhood myths have been made into movies showing the way people lived in the past. Creating value through the cultural landscape. Thai society has diverse cultural areas. That will lead to research and create educational and cultural policies. The cultural landscape has been transferred to the new generation to create innovations for national development.